2017
DOI: 10.1017/s1759078717000563
|View full text |Cite
|
Sign up to set email alerts
|

A 20 GHz microwave heater for digital microfluidic

Abstract: This paper reports on a microwave heater at 20 GHz for digital microfluidics. It allows rapid heating of nanoliter fluid samples and simultaneous temperature monitoring by correlating the reflection coefficient of the heater with the temperature dependency of the relative permittivity of the lossy fluid under consideration, in this case demineralized water. Microwave heating was performed with power levels of 20 and 23 dBm at the on-wafer probe tips on samples of 500 nL. Temperature measurements were carried o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…On the other hand, the utilization of on-chip thermal unit miniaturized outline dimensions of the devices, which is beneficial for POCT. Frankly, apart from the contact-based Joule heating, some oncoming technologies are promising and attract interest from many communities, such as surface acoustic waves, 31 microwave 32 and lasers. 33 However, their drawbacks in terms of fabrication, integration, cost, and accuracy of the position and temperature control, etc.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the utilization of on-chip thermal unit miniaturized outline dimensions of the devices, which is beneficial for POCT. Frankly, apart from the contact-based Joule heating, some oncoming technologies are promising and attract interest from many communities, such as surface acoustic waves, 31 microwave 32 and lasers. 33 However, their drawbacks in terms of fabrication, integration, cost, and accuracy of the position and temperature control, etc.…”
Section: Resultsmentioning
confidence: 99%
“…The common solutions are based on optical [15][16][17], electrochemical [18], acoustical [19] and electromagnetic [20][21][22][23][24] components. Moreover, the microreactors designed for continuous, as well as for digital microfluidics can be found in the literature [25][26][27]. The last area typically includes circuits that are characteristic of the microwave technique.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative solution for temperature control is microwave heating as it does not rely its operation on heat conduction-heat is generated by the liquid itself once it is exposed to an alternating electric field. Several research groups have reported microwave heating devices [8][9][10][11][12][13][14][15][16][17][18] for digital and continuous microfluidics in the past decade. For continuous flow microfluidics, the focus has been on heating of individual pico-and nano-liter droplets flowing through fluidic channels [8][9][10][11][12], microliter volumes in wells placed along fluidic channels [13,14], or on heating of liquid located over the complete fluidic chip [15,16].…”
Section: Introductionmentioning
confidence: 99%